2012
DOI: 10.1088/0004-637x/756/2/173
|View full text |Cite
|
Sign up to set email alerts
|

MULTI-WAVELENGTH OBSERVATIONS OF THE ENDURING TYPE IIn SUPERNOVAE 2005ip AND 2006jd

Abstract: We present an observational study of the Type IIn supernovae (SNe IIn) 2005ip and 2006jd. Broadband UV, optical, and near-IR photometry, and visual-wavelength spectroscopy of SN 2005ip complement and extend upon published observations to 6.5 years past discovery. Our observations of SN 2006jd extend from UV to mid-infrared wavelengths, and like SN 2005ip, are compared to reported X-ray measurements to understand the nature of the progenitor. Both objects display a number of similarities with the 1988Z-like sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
247
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 173 publications
(272 citation statements)
references
References 80 publications
24
247
1
Order By: Relevance
“…For example, the X-ray luminosities of ∼10 37 erg s −1 in 0.1-10 keV at one year after the explosion is expected in our 10 −4 M yr −1 model with the formalism of Fransson et al (1996). SN IIn 2005ip, which had a similar optical luminosity to our ecSN model at the early plateau (Stritzinger et al 2012), had an X-ray luminosity of 10 41 erg s −1 in 0.1-10 keV at one year after the explosion (Katsuda et al 2014). Thus, optically bright but X-ray-faint SNe IIn can be promising candidates for ecSNe.…”
Section: Other Supernovaesupporting
confidence: 70%
“…For example, the X-ray luminosities of ∼10 37 erg s −1 in 0.1-10 keV at one year after the explosion is expected in our 10 −4 M yr −1 model with the formalism of Fransson et al (1996). SN IIn 2005ip, which had a similar optical luminosity to our ecSN model at the early plateau (Stritzinger et al 2012), had an X-ray luminosity of 10 41 erg s −1 in 0.1-10 keV at one year after the explosion (Katsuda et al 2014). Thus, optically bright but X-ray-faint SNe IIn can be promising candidates for ecSNe.…”
Section: Other Supernovaesupporting
confidence: 70%
“…Besides 7 typical SN II and Ia, the following four SNe had more precise classifications: SN 2000ft was discovered in NGC 7469 by using radio observations and showed similar evolution properties than other compact radio sources identified as SN II (Alberdi et al 2006); SN 2000cb showed similar photometric behaviour than SN 1987A, which are thought to be SN II resulting from the explosion of blue supergiants (Pastorello et al 2005;Taddia et al 2012); SN 1993R was typed as a peculiar SN similar to the subluminous SN Ia class 1991bg-like, but with stronger Ca II NIR triplet (Filippenko & Matheson 1993). Finally, SN 2005ip spectra showed that it was interacting with the surrounding circumstellar medium and it was typed as SN IIn (Stritzinger et al 2012).The programs that proposed the observations of these 5 galaxies, observation periods, exposure times, and seeing at the time of observations are summarized in Table 1. MUSE delivers an impressive set of ∼100,000 spectra per pointing covering most of the optical domain. For NGC 6754, the observations were divided in two pointings, one for each eastern and western part of the galaxy.…”
Section: Observationsmentioning
confidence: 99%
“…For example, the shape of the light curves of type IIn SNe depend on the initial radius of the star, the ejecta mass and the explosion energy of the SNe, and the density structures of the ejecta and CSM (van Marle et al 2010;Moriya et al 2013;Taddia et al 2015). The range of potential progenitors is large and may include any star with a significant pre-SN eruption, for example, red supergiants or luminous blue variables (LBVs) (Gall et al 2011;Stritzinger et al 2012;Van Dyk 2013). Lucy et al (1991) noted a shallow optical extinction curve inferred from the light curves of SN 1987A.…”
Section: Introductionmentioning
confidence: 99%
“…While this was inferred from significant attenuation of the red wings and corresponding blueshifts of the centroids of the hydrogen emission lines, no broadband color changes were detected in the light curves. SN 2005ip was discovered on 2005 November 5.2 UT in the Scd galaxy NGC 2906 (Boles et al 2005;Stritzinger et al 2012). The measured redshift of the host galaxy is 0.00714, corresponding to a luminosity distance of about 30 Mpc (de Vaucouleurs et al 1991;Smith et al 2009).…”
Section: Introductionmentioning
confidence: 99%